SOFS APP / Farhad Imam Iffat Fansuri Mushadat ... [et al.] - Fansuri Mushadat, Farhad Imam Iffat; Shamsulraji, Nurul Jannah Athirah; Mohd Aidil, Anis Umaira; Roslan, Aleeya Raihanah; Ahmad Syukri, Ahmad Umar Qayyum (Faculty of Computer and Mathematical Sciences, 2021)
SOFS APP or Solat Focus Smart Application is an innovation of application used during the performance of “solat” or prayer by Muslims especially in form of “Jemaah” or congregation . Conventionally we will see an “Imam” or the leader of a prayer referring to a big-sized Quran of 24” x 12” let opened on a stand before him to read verses of Al-Quran. With the invention of SOFS APP , the use of “Masyhaf ’ ( Al-Quran) is optional. The imam can instead refer to a screen of a tablet or laptop placed in front of him to recite A1 Quran. The app is also equipped with a remote for the “Imam” to turn on the pages. SOFS APP is actually an alternative to the use of Masyhaf ( Al- Quran ) during a prayer. SOFS APP is not merely a screen of A1 Quran but a complete networking that connects the Imam to the “ma’mum” ( persons who follow the leader to perform Solat) during the prayer or whoever using the QR code registered for the link . We normally see a person holding Al-Quran while performing a prayer to trace long recitation of Quran by the “Imam”. Therefore , with the use of SOFS APP, a “ma’mum” can just hold a smart phone . Even a late follower can just use a smart phone to read the QR code which is pasted at the “Solat Hall “ and automatically it will detect the page read by the leader or “Imam”. SOFS APP has obtained approval from Terengganu Mufti Department and this innovation is highly recommended to be used in mosques.